Upgrades of the RFX-mod reversed field pinch and expected scenario improvements. (7th June 2019) - Marrelli, L.; Cavazzana, R.; Bonfiglio, D.; Gobbin, M.; Marchiori, G.; Peruzzo, S.; Puiatti, M.E.; Spizzo, G.; Voltolina, D.; Zanca, P.; Zuin, M.; Berton, G.; et al.
Abstract: RFX-mod is a Reversed Field Pinch device that allowed performing experiments in regimes with a plasma current up to 2 MA, thanks to its MHD active control system. Experiments have shown that improved plasma performances are obtained when in the resonant part of the m = 1 spectrum one dominant tearing mode is much higher than the other secondary ones (quasi single helicity states). Tearing modes play a crucial role in determining energy and particle transport. Based on the present understanding of the interplay between passive conductive boundaries and tearing modes in an RFP, an upgrade of RFX-mod machine assembly has been designed, dubbed RFX-mod2, and it is now being implemented. The highly resistive Inconel vessel will be removed, graphite tiles will be attached to the copper stabilizing shell and the stainless steel support structure will be modified in order to be vacuum tight. In RFX-mod2, the shell-plasma proximity decreases from b / a = 1.11 to b / a = 1.04 and copper, instead of Inconel, will be the continuous conducting structure nearest to the plasma. MHD non-linear simulations show that secondary tearing modes amplitude and the edge bulging due to their phase locking will decrease; moreover the plasma current threshold for tearing modes wall locking will also significantly increase.